COMPLEMENTARY FINDINGS ON THE ANTIMALARIAL ACTIVITY AND TOXICITY OF METHYLENE BLUE HALLAZGOS COMPLEMENTARIOS SOBRE LA ACTIVIDAD ANTIMALÁRICA DEL AZUL DE METILENO Y SU TOXICIDAD - Giovanny GARAVITO (Universidad de Antioquia, 2008)
Methilene blue was reported as the first synthetic antimalarial by Ehrlich in 1881. It is currently no longer used for that purpose but it should be reconsidered since new economic alternatives are urgently needed in the arsenal of antimalarial drugs. The antimalarial activity of methylene blue is investigated here in vivo against rodent malaria parasites. 15 mg/kg daily dose of methylene blue inhibits 50% of the erythrocytic parasite growth of Plasmodium berghei and P. yoelii nigeriensis, while on hepatic stages of P. yoelii yoelii is almost inactive. In cell culture experiments with the lymphoblast-like BJAB cells line, it is 20 times more cytotoxic than chloroquine. Nevertheless, methylene blue shows a similar selectivity index as chloroquine against strains of different level of sensitivity of P. falciparum original from different geographical areas. En 1881, Ehrlich reportó el azul de metileno como el primer antimalárico sintético, pero dejo de ser empleado con este propósito; el debe ser reconsiderado pues son necesarias con urgencia nuevas alternativas de bajo costo, en el arsenal de medicamentos antimaláricos. En este trabajo la actividad antimalárica del azul de metileno es evaluada in vivo frente a parásitos de malaria murina. Una dosis de 15 mg/kg/día inhibe el 50% del crecimiento eritrocítico parasitario de Plasmodium berghei y P. yoelii nigeriensis, en tanto que es prácticamente inactivo frente a los estadios hepáticos de P. yoelii yoelii. Sobre un cultivo de la línea celular linfoblástica BJAB, el azul de metileno es 20 veces más citotóxico que la cloroquina, no obstante el azul de metileno presenta valores de índice de selectividad del mismo nivel que la cloroquina, frente a varias cepas de P. falciparum de diferentes niveles de sensibilidad y provenientes de diferentes lugares geográficos.